Yakemys multiporcata n. g. n. sp., a Large Macrobaenid Turtle from the Basal Cretaceous of Thailand, with a Review of the Turtle Fauna from the Phu Kradung Formation and Its Stratigraphical Implications - Haiyan Tong; Phornphen Chanthasit; Wilailuck Naksri; Pitaksit Ditbanjong; Suravech Suteethorn; Eric Buffetaut; Varavudh Suteethorn; Kamonlak Wongko; Uthumporn Deesri; Julien Claude (Diversity, 2021)
Yakemys multiporcata n. g. n. sp. is described on the basis of shell elements from the upper part of the Phu Kradung Formation (basal Cretaceous), Khorat Plateau, NE Thailand and assigned to Macrobaenidae. The new taxon is unusually large for an early macrobaenid (with an estimated carapace length about 70 cm) and is characterized by a large, rounded, low shell, the presence of a midline keel and numerous additional strong ridges on the carapace, the anterolateral margin upturned to form a gutter, posterolateral peripherals mesiolaterally expanded, narrow vertebrals, the vertebral 4 triangular and narrowed posteriorly, a greatly reduced plastron with a short bridge, an oval and elongate entoplastron with reduced ventral exposure, and strip-shaped epiplastra. The discovery of a macrobaenid turtle provides further support for an Early Cretaceous age for the upper part of the Phu Kradung Formation.